2017
DOI: 10.1159/000475936
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Three Different Volumes of Levobupivacaine for Caudal Block in Children Undergoing Orchidopexy and Inguinal Hernia Repair

Abstract: Objective: The aim of this study was to compare the efficacy of 3 different volumes of 0.25% levobupivacaine caudally administered on the effect of intra- and postoperative analgesia in children undergoing orchidopexy and inguinal hernia repair. Subjects and Methods: Forty children, aged 1-7 years, American Society of Anesthesiologists (ASA) physical status I and II, were randomized into 3 different groups according to the applied volumes of 0.25% levobupivacaine: group 1 (n = 13): 0.6 mL∙kg-1; grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
1
2
0
1
Order By: Relevance
“…The expected adverse reactions were inadequate analgesia, local reaction to the anaesthetic, and delayed urine derivation in the post-operative period (albeit very rare in children). However, adverse reactions were not reported, which is in line with previous studies (7,9,20,21).…”
Section: Interpretation Of the Study Resultssupporting
confidence: 91%
“…The expected adverse reactions were inadequate analgesia, local reaction to the anaesthetic, and delayed urine derivation in the post-operative period (albeit very rare in children). However, adverse reactions were not reported, which is in line with previous studies (7,9,20,21).…”
Section: Interpretation Of the Study Resultssupporting
confidence: 91%
“…Two studies evaluated the efficacy of caudal epidural anesthesia on postoperative analgesia in children undergoing orchiopexy and inguinal hernia repair. 30 , 40 One study evaluated three different volumes of 0.25% levobupivacaine (low: 0.6 mL/kg; middle: 0.8 mL/kg; and high: 1.0 mL/ kg) and reported that the postoperative analgesic consumption at 6, 12, and 24 hours following surgery did not differ among groups. The postoperative pain was evaluated using the CHIPPS instrument which was not statistically different among groups at any time period.…”
Section: Resultsmentioning
confidence: 99%
“…Previous RCTs showed that caudal block of 1 mL kg –1 and <1 mL kg –1 had similar analgesic effects in inguinal hernia repair, orchiopexy, and circumcision. 101,102 This might be explained by the small correlation between the caudal block volume and the cranial spread of local anesthetic under ultrasound assessment. 103 Although caudal block with 1.5 mL kg –1 reaches T6 under fluoroscopy and increases analgesic effects compared with 1.0 mL kg –1 in children undergoing orchiopexy, 104 such a volume was reported to cause immediate and major reductions in cerebral blood flow and cerebral regional oxygenation in infants <3 months.…”
Section: Discussionmentioning
confidence: 99%